Analysis Pt X Employee Welfare Through A Case Study Of Minimum Wage Demands - Muhammad Nur Sidik, Muhammad Nur Sidik; Wiradendi Wolor, Christian; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study investigates the impact of minimum wage demands on employee welfare at PT X, where wages are currently below the provincial minimum wage. The objectives were to analyse the state of employee welfare, understand the implications of the wage demands, and explore the factors driving the demands. The objectives focused on providing insights to improve employee welfare and enhance industrial relations within the company. This study employed a descriptive qualitative research methodology, using semi-structured interviews and observation to collect data. The participants were long-term employees at the Cakung branch of PT X, selected through purposive sampling. This research aims to explore the relationship between minimum wage demands and employee well-being, providing in-depth insights into their experiences and perspectives on workplace conditions and compensation. Findings show that employees at PT X experience significant financial stress due to wages below the minimum wage, which impacts their overall well-being. Many employees reported difficulties in fulfilling basic needs, such as food and shelter. The study highlights a strong correlation between minimum wage demands and employee satisfaction, emphasising the need for improved compensation and working conditions. The study concludes that addressing minimum wage demands is critical to improving employee well-being at PT X. Recommendations include implementing a competitive wage structure, regular salary reviews, and fostering open communication between management and employees. By prioritising fair compensation and improving working conditions, PT X can increase employee satisfaction, productivity, and overall organisational performance.